Projeto e estudo de caso de um enlace ponto a ponto no regional Mossoró - Dantas Neto, Pedro Moisés (Universidade Federal Rural do Semi-Árido, 2021)
This work presents a case study that quantitatively and qualitatively analyzes the performance of a point-to-point radio link in a microwave frequency, 7.5GHz band licensed by Anatel. The project was developed by comparing the prediction of the real link made by a software, called Celplanner, and mathematical calculations. The results obtained with the simulation in Celplanner and with the mathematical equation demonstrate the accuracy of the prediction software in the characterization of radio links by the proximity of the real values presented in the real system monitoring
Keywords: Enlace de rádio; Celplanner; Projeto e estudo de caso; Radio link; Celplanner; Project and case; ENGENHARIAS::ENGENHARIA ELETRICA